Plate dryer / Mohamad Rozi Md Said ... [et al.] - Md Said, Mohamad Rozi; Ruslan, Mohamad Norman; Zulkefley, Mohd Safwan (2005)
The main objective of the project is being included in the programs is to enable the student to convert the theory knowledge into a vital hands-on practical in term of the entire engineering prospects. The project is actually to provide student with certain skills in engineering such as welding process, milling, how to operate the lathe machine etc. it's important to build up the student confident, ability and skills. It does also build the student creativity to produce high quality products. Student is thought to work as a team in order to produce better products